MR Imaging in the Diagnosis of Desmoplastic Infantile Tumor: Retrospective Study of Six Cases - Trehan, Guillaume; Bruge, Helene; Vinchon, Matthieu; Khalil, Chadi; Ruchoux, Marie M.; Dhellemmes, Patrick; Ares, Gustavo Soto (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Desmoplastic infantile tumors (DITs) are rare supratentorial tumors of infancy with a favorable prognosis. Radiologic and histologic features of DIT are misleading, and DIT may be misinterpreted as a malignant lesion. We have studied the usefulness of MR imaging in the diagnosis of these tumors.METHODS: Between 1995 and 2002, six DITs were diagnosed in young children at our institution. Neuroimaging, age at diagnosis, sex, clinical presentation, symptoms duration, follow-up, and development were studied retrospectively. Contrast-enhanced CT and MR images were available. MR study included T1-, T2-, and postgadolinium T1-weighted sequences in the axial, sagittal, and coronal planes.RESULTS: These tumors were massive and predominantly cystic, with preferential frontal and parietal involvement. Typically, a DIT appears as a hypointense cystic mass with an isointense peripheral solid component on T1-weighted MR images. The peripheral solid component enhances after gadolinium administration. On T2-weighted MR images, the cystic component is hyperintense and the solid portion isointense or heterogeneous. The cystic portion is usually located deep inside the lesion, whereas its solid portion is peripheral. Meningeal enhancement and thickening adjacent to the solid portion of the tumor, calcifications, bone abnormalities adjacent to the tumor consisting of thinning and deformation were noted in 50% of our cases. Edema was usually absent or moderate. Median follow-up was 32 months, and no recurrence was noted except for one atypical case with incomplete excision, which led to the patient’s death.CONCLUSION: Despite their malignant appearance, MR imaging features of DIT may help in the diagnosis and obviate unnecessary chemotherapy or radiation therapy.